Formation and development of the sports tourism in Ukraine - S. Kudelina; A. Hetmanenko; O. Nikolaieva; V. Khomutov (Kazimierz Wielki University, 2022)
The article discusses the features of the development of sports tourism. It is proved that the beginning of the new millennium was marked by the rise of the world tourist movement. Under the influence of rapid development of infocommunication technologies and international economic relations tourism has become one of the most representative branches of the world economy. The article proves that the development of the recreational and tourist complex of Ukraine should become a priority direction of the national economy and culture, an important factor in increasing the international prestige of the country, a source of socio-economic development of the regions, an important condition for preserving the historical and cultural heritage.